2020
DOI: 10.1016/j.dcn.2020.100858
|View full text |Cite
|
Sign up to set email alerts
|

Maternal odor reduces the neural response to fearful faces in human infants

Abstract: Maternal odor is known to play an important role in mother-infant-interaction in many altricial species such as rodents. However, we only know very little about its role in early human development. The present study therefore investigated the impact of maternal odor on infant brain responses to emotional expression. We recorded the electroencephalographic (EEG) signal of seven-month-old infants watching happy and fearful faces. Infants in two control groups exposed to no specific odor (control 1) or the odor o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Although speculative, a possibility is that the psychobiological state of postpartum leads to the release of a common pattern of chemical compounds in the body odor of postparturient women, to which infants would have responded categorically. In any case, a more specific response to the mother's body odor was reported in older infants during the processing of emotional facial expressions (Jessen, 2020). Compared to the body odor of another mother (or a control odor), the exposure to their own-mother's body odor reduced the typical neural response for fear faces in 7-month-olds, suggesting that maternal body odor can impact emotional learning in infancy (Jessen, 2020), although the underpinning mechanisms remain unclear.…”
Section: Developmental Aspects: Olfaction-to-vision Influences In Infancymentioning
confidence: 84%
“…Although speculative, a possibility is that the psychobiological state of postpartum leads to the release of a common pattern of chemical compounds in the body odor of postparturient women, to which infants would have responded categorically. In any case, a more specific response to the mother's body odor was reported in older infants during the processing of emotional facial expressions (Jessen, 2020). Compared to the body odor of another mother (or a control odor), the exposure to their own-mother's body odor reduced the typical neural response for fear faces in 7-month-olds, suggesting that maternal body odor can impact emotional learning in infancy (Jessen, 2020), although the underpinning mechanisms remain unclear.…”
Section: Developmental Aspects: Olfaction-to-vision Influences In Infancymentioning
confidence: 84%
“…The presence of the scent of the mother alone has also been demonstrated to decrease the threat response in children (Jessen, 2020). In children, as found in rodent research, the presence of maternal stimuli suppresses amygdala reactivity, with this effect waning with maturation (Gee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a fear odour facilitates the detection of fearful expressions over other negative expressions (Kamiloglu et al, 2018 ; cf. Jessen, 2020 ). Meanwhile, Zhou and Chen ( 2009 ) found that the chemosignal of fearful sweat biased women toward interpreting ambiguous facial expressions as more fearful, but has no effect when the facial emotion was more obvious (see also Prehn-Kristensen et al, 2009 ).…”
Section: The Influence Of a Person’s Natural Body Odour On Multisensory Person Perceptionmentioning
confidence: 99%